More Than Meets the Eye: Ingredient Prevalence and Patch Test Relevance in UK Micellar Waters - Zara Ali; Livia Francine Soriano (Clinical and Experimental Dermatology, 2026)
A survey of 111 UK micellar waters found that many contain recognised allergen groups, including fragrances, botanicals, preservatives, and surfactants, even when marketed for sensitive skin. The findings highlight potential gaps in routine patch testing and suggest clinicians should consider micellar water use and supplementary patch testing in patients with persistent facial or eyelid eczema.